2021
DOI: 10.3390/machines9070127
|View full text |Cite
|
Sign up to set email alerts
|

Finding the Best Programmable PWM Pattern for Three-Level Active Front-Ends at 18-Pulse Connection

Abstract: The existing publications on the analysis of power quality indicators in modern electric power supply systems are void of a comprehensive approach to improving these indicators in power systems by implementing multipulse connections. To the authors’ knowledge, this paper is the first to analyze current harmonic distortions in an 18-pulse connection of three-level active front-ends (AFE) featuring a programmed PWM. Raw data were obtained from, and current quality was analyzed for the power circuit of the main e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 30 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Figures 8-10 illustrate several SHE solutions by built-in function fsolve in MATLAB (MathWorks, 2017b, Natick, MA, USA) for six-pulse, twelve-pulse, and eighteen-pulse connection schemes [102], respectively. It is important to note that this method has the characteristics of fast convergence speed and high precision when a proper initial value is given.…”
Section: Results Of She Implementationmentioning
confidence: 99%
“…Figures 8-10 illustrate several SHE solutions by built-in function fsolve in MATLAB (MathWorks, 2017b, Natick, MA, USA) for six-pulse, twelve-pulse, and eighteen-pulse connection schemes [102], respectively. It is important to note that this method has the characteristics of fast convergence speed and high precision when a proper initial value is given.…”
Section: Results Of She Implementationmentioning
confidence: 99%
“…The relevant studies in the area have shown that the higher the m value, the lower the THD of the converter output voltage [19][20][21][22][23]. In practice, the m value close to 1 (if we describe a range from 0 to 4/π) is chosen while providing a margin for maintaining stable AFE and VSI operation in dynamic modes (a voltage drop in the DC link during shock application of the electric drive load) [24][25][26][27].…”
Section: Eafe Egmentioning
confidence: 99%
“…It was designed to gradually eliminate lower-order harmonics according to a given semiconductor module switch number. Herein, we will consider the SHE PPWM since it is used most frequently in practice [6][7][8].…”
Section: Introductionmentioning
confidence: 99%